Repetition: A Process of Destroying the Narrative Unity in Abdelkader Djemais Saison De Pierres (Global Journal of Human-Social Science, 2019)
In Saison de pierres Abdelkader Djemai makes the repetition process one of his principles of composition narrative sequences are repeated repeating themselves thus openly provoking the traditional novel The reader at first glance thinks he is reading the same text but after concentration there are many variations between the two narrative passages By using the repetition process Abdelkader Djemai wants to introduce a new reflex in the reader to test his memory by using his insight and intelligence Repetition allows the author to say and repeat in several copies the same idea the same event the same experience offering a multitude of perspectives and invoking maximum concentration
Keywords: repetition; reflection; destruction; construction; reader